2022
DOI: 10.1186/s13098-022-00799-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between hypoglycemia and dementia in patients with diabetes: a systematic review and meta-analysis of 1.4 million patients

Abstract: Background Diabetes mellitus (DM) is known to be a risk factor for dementia. However, it is unclear if hypoglycemic events play a role in the risk of dementia. We aimed to systematically review evidence on the risk of dementia in DM patients based on prior hypoglycemic events. Methods PubMed, Embase, ScienceDirect, CENTRAL, and Google Scholar databases were searched till 15th November 2021 for cohort studies assessing the risk of dementia based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…This data, however, has not always been consistent, as other studies have shown no evidence that hypoglycemia contributes to cognitive impairment in older adults [32][33][34]. Furthermore, the frequency of hypoglycemic events and the risk of dementia has not been established, with the same pooled analysis failing to demonstrate a linear relationship between the number of hypoglycemic events and the risk of dementia [31].…”
Section: Key Pointsmentioning
confidence: 84%
See 1 more Smart Citation
“…This data, however, has not always been consistent, as other studies have shown no evidence that hypoglycemia contributes to cognitive impairment in older adults [32][33][34]. Furthermore, the frequency of hypoglycemic events and the risk of dementia has not been established, with the same pooled analysis failing to demonstrate a linear relationship between the number of hypoglycemic events and the risk of dementia [31].…”
Section: Key Pointsmentioning
confidence: 84%
“…Various cohort studies [26][27][28][29][30] have shown that severe antecedent hypoglycemia, particularly in those on insulin therapy, may be an important contributor to the increased risk of dementia and cognitive decline in individuals with diabetes [28]. A quantitative pooled analysis from 10 observational cohort studies between 2009 and 2021 (n ¼ 1 407 634 individuals with T2DM and T1DM) demonstrated that those with a prior severe hypoglycemic event had a 44% increased risk of dementia compared with those who had no reported hypoglycemia (hazard ratio 1.44; 95% CI 1.26-1.65, I 2 ¼ 89%, P < 0.00001) [31]. This data, however, has not always been consistent, as other studies have shown no evidence that hypoglycemia contributes to cognitive impairment in older adults [32][33][34].…”
Section: Key Pointsmentioning
confidence: 99%
“…Several other explanations may be suggested besides methodological differences for the disparate findings. For instance, recent studies showed that the association between DM and dementia may be modified by the concurrent antidiabetic agents used 16 and the possible episodes of hypoglycaemia, 15 which were mostly not considered or controlled in previous observational studies or meta‐analyses. For people with prediabetes, antidiabetic agents are generally not applied and episodes of hypoglycaemia are rare, which both have minimal influences on the association between prediabetes and the incidence of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…15 Moreover, a recent metaanalysis suggests that DM hypoglycaemic episodes in patients with DM may further increase the risk of dementia as compared to DM patients without hypoglycaemia. 16 Collectively, these findings suggest the complexity of the association between glycaemic disorder and dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation